Implementing the African Continental Free Trade Area (AfCFTA): The Effects of Trade Procedures on Trade Flows - Manfred Kouty (Research in Applied Economics, 2024)
In January 2018, the 10th African Union (AU) Summit of African Heads of States and Governments was held in Kigali. At this occasion, 44 countries had signed the African Continental Free Trade Area (AfCFTA) agreement. In this study, it is pointed out that the implementation of AfCFTA cannot be done without harmonized trade procedures. Using a gravity model of 49 African countries over the 2010-2015 periods, the study estimates the impact of inefficient trade procedures on intra-African trade. The results show that trade procedures such as the number of documents required to import goods and Border compliance negatively affect intra-African trade. This suggests the need of harmonization and rationalization of trade procedures to boost intra-African trade.